2008
DOI: 10.1038/ijo.2008.12
|View full text |Cite
|
Sign up to set email alerts
|

Does maternal concern about children's weight affect children's body size perception at the age of 6.5?—A community-based study

Abstract: Objective: Though overweight is often established by school entry, not all mothers of such children report weight concerns. Enhancing concern might assist lifestyle change, but could lead to child body dissatisfaction. We investigated (i) perceived/ desired body size and body dissatisfaction in mothers and their 6.5-year-old children, and (ii) the impact of earlier maternal concern about overweight on children's body mass index (BMI) status and body dissatisfaction. Design: Prospective community study. Setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
1
13
0
3
Order By: Relevance
“…Generalizability beyond a rather homogenous Latino population is limited. Though findings were very similar to previous studies [5, 11, 32, 33], the sample was relatively small and comprised predominately of mothers of Mexican heritage, with low acculturation to the U.S., who themselves were overweight or obese. The limited variability of CFQ scores and BMI in this homogenous sample also limits the range of possible correlations between the two distributions.…”
Section: Discussionsupporting
confidence: 86%
“…Generalizability beyond a rather homogenous Latino population is limited. Though findings were very similar to previous studies [5, 11, 32, 33], the sample was relatively small and comprised predominately of mothers of Mexican heritage, with low acculturation to the U.S., who themselves were overweight or obese. The limited variability of CFQ scores and BMI in this homogenous sample also limits the range of possible correlations between the two distributions.…”
Section: Discussionsupporting
confidence: 86%
“…In Australia, 88% and 90% of mothers of overweight and obese children, respectively, underestimated their children's weight status. 15 While in Canada, a study comparing parents' and doctors' perception in relation to their children's weight described that 47% of parents underestimated their children's weight status. 16 In Mexico, it has been reported that more than 79% of parents of overweight or obese children underestimated their children's weight status; 9 in addition, 83% of mothers of overweight or obese children underestimated their children's weight.…”
Section: Discussionmentioning
confidence: 99%
“…This might be particularly true for girls, whose parents have been shown to be more aware of a high BMI in their child than parents of boys. 18 In contrast, parents who are overweight themselves may underestimate their child' s overweight and may be less likely than normal-weight parents to adjust their parenting in response to child overweight. 19,20 Disentangling associations between parenting and child BMI, and understanding how these develop over time, requires repeated measures of parenting and child BMI.…”
mentioning
confidence: 99%